A characterisation framework of energy services offered by energy service companies. (15th October 2022) - Cagno, Enrico; Franzò, Simone; Storoni, Elena; Trianni, Andrea
Highlights: Review of energy services, technologies, and markets by ESCOs. Novel framework to assess energy services, technologies, and markets by ESCOs. Multiple case study within ESCOs mapping services, technologies, and markets. Empirical assessment of current and prospective business opportunities within ESCOs. Abstract: Energy Service Companies (ESCOs) are key players in the provision of energy services, hence they are considered strategic means to foster energy efficiency across countries. Nonetheless, despite the undergoing radical transformation within the ESCOs industry - especially the increasing tendency to bundle services, recent research capable to capture such evolution and development, in terms of services, technologies, and markets targeted by ESCOs is scarce. The present study aims at fulfilling the outlined research gaps by developing a novel framework for the classification and characterisation of services offered by ESCOs, as well as technologies and markets addressed. Services are characterised into nine categories, namely: preliminary analysis; project assessment; project contracting; project financing; project technology management and project supervision; energy procurement, management of incentives and regulations, and other services. The developed framework is then preliminary tested by applying it to a sample of eight Italian ESCOs to assess its completeness and usefulness. Results show the capability of the framework to adequately detail and map clusters of services-technologies-markets addressed by ESCOs, also identifying areas for future business opportunities for ESCOs themselves. The study concludes with recommendations for industry and policymaking on future efforts to promote energy services, as well as future research in this area.